From observation to action A video-based professional development resource for teachers of English as a foreign language (United States, 2013)
Shaping the Way We Teach English: From Observation to Action is a series of video-based training materials for English as a Foreign Language (EFL) educators. These materials provide the opportunity for teachers to observe 13 full-length videos of real classes and guide them to evaluate the teaching practices, adapt the materials and techniques to suit their own teaching needs, act upon the insights gained by implementing new ideas, and reflect on these ideas to develop a variety of pedagogical skills.
Keywords: English language,Tiếng Anh; Study and teaching,Dạy và học